A Philosophical Analysis of the Recent Controversy about “Islamo-leftism” in French Academia - Stamenkovic, Philippe (Ruch Filozoficzny, 2022)
In February 2021, the French Minister of Higher Education and Research, Frédérique Vidal, ordered an inquiry – to be led by the French National Centre for Scientific Research – about the alleged “Islamo-leftism” (islamo-gauchisme) which, according to her, was corrupting French academia. Vidal’s concern was, purportedly, to distinguish “what falls under academic research and what falls under militancy and opinion”. She had in mind, in particular, recent interdisciplinary fields in the social sciences, such as Postcolonial Studies. Her statements caused a controversy in French academia as well as outside. The goal of this paper is to present this controversy and analyse it in light of the philosophical literature on autonomy of, and values in, science. After recalling the political and institutional context of the controversy (1st part), I present Vidal’s intervention (2nd part) and various reactions to it, which can roughly be classified pro and contra Vidal’s statements (3rd part). I then provide a philosophical discussion of the controversy (4th part), by recalling the philosophical debate to which it is related (the autonomy of, and the values in science), and analysing the assumptions, arguments and actions of both camps. I show in particular that a political intervention inside the very production of academic knowledge implies a strong risk of censorship (whether self-inflicted, intra-academic or extra-academic), and that letting academia self-regulate itself with respect to the validation of knowledge remains the best way to go. I conclude with the deeper questions raised by this controversy: the social role of universities, and the institutional aspects of scientific knowledge validation.